2018
DOI: 10.3126/banko.v27i3.20556
|View full text |Cite
|
Sign up to set email alerts
|

Linking silvicultural aspects of pro-poor leasehold forestry for socio-economic benefits to the poor and vulnerable communities

Abstract: Government of Nepal has adopted different models like community forestry, leasehold forestry, collaborative forestry, buffer zone community forestry and public land agroforestry for management of forest resources. Poor focused leasehold forestry is only the approach adopted since early 1990 that has two major objectives: livelihood improvement and environmental conservation. Forest user groups of 5–15 households (HHs) are provided with part of national forests for a period of initial lease of 40 years. Leased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…People can enhance their income through IGAs such as animal husbandry, apiculture, Sericulture, NTFPs cultivations, etc. It also promotes the participation of women and makes a remarkable shift towards sharing decisionmaking among men and women (Yadav and Dhakal 2000;Ohler, 2003). As a result, the LF program has been successful in improving the various capitals of the poor's livelihoods by increasing livestock production and restoring degraded land.…”
Section: Introductionmentioning
confidence: 99%
“…People can enhance their income through IGAs such as animal husbandry, apiculture, Sericulture, NTFPs cultivations, etc. It also promotes the participation of women and makes a remarkable shift towards sharing decisionmaking among men and women (Yadav and Dhakal 2000;Ohler, 2003). As a result, the LF program has been successful in improving the various capitals of the poor's livelihoods by increasing livestock production and restoring degraded land.…”
Section: Introductionmentioning
confidence: 99%
“…Leasehold forestry is promoted with the twin objectives of reducing poverty and restoring forests. Studies have shown that this programme has contributed greatly to improving the household income of the poor communities as well as restoring forests (Ohler 2003;Baral et al, 2012;Poudyal et al, 2018;Kafley and Pokharel 2017;Yadav et al, 2018). Improved forest conditions can contribute greatly to carbon sequestration and might provide a platform for carbon trade (Dhungana, 2008), which will supplement the income of the users.…”
Section: Introductionmentioning
confidence: 99%